Study protocol for a randomized single-center cross-over study: Dapagliflozin treatment in recurring kidney stone patients - Haris Omić; Michael Eder; Harald Herkner; Christian Seitz; Željko Kikić; Tarek Arno Schrag (PLoS ONE, 2025)
Introduction Urolithiasis is one of the most common diseases worldwide, characterized by high morbidity and significant treatment-related costs, with a rising prevalence of up to 20%. The relapse rate within the first 10 years after initial treatment is estimated to be about 60%. Given the increasing prevalence, healthcare-related costs associated with urinary tract stones in the USA are expected to reach up to US $1.24 billion annually by 2030. Current prophylactic therapy for urolithiasis recurrence includes lifestyle modifications, citrate supplementation, and pharmaceuticals. However, a high number of cases remain unresponsive to available pharmacological therapies. Though initially developed for the treatment of Diabetes mellitus, SGLT-2 inhibitors have shown promise in decreasing cardiac and renal endpoints across multiple indications. Recent registry studies have indicated that patients receiving SGLT-2 inhibitors exhibit lower rates of urolithiasis incidence, suggesting a potential reduction in recurrence rates and associated mortality. Objectives We hypothesize that SGLT-2 inhibitors (Dapagliflozin), owing to their multiple pleiotropic effects, may offer a viable treatment option for the prophylaxis of high-risk calcium oxalate kidney stones and reduce urinary calcium oxalate output. Methods This study will proceed in two phases: an exploratory phase and a randomized controlled phase. In the exploratory phase, 22 participants with indications for dapagliflozin treatment will be evaluated before and after treatment initiation to ascertain the concrete effect size regarding oxalate and calcium-sparing effects. This data will inform the calculation of the study sample size (ranging from 17 to 104 participants) to include high-risk calcium oxalate kidney stone formers in a randomized controlled crossover study design. Treatment phases—one with dapagliflozin and one with placebo—will alternate with wash-out phases involving placebo. The primary outcome is the reduction of oxalate excretion in 24-hour urine samples compared to baseline values after 8 weeks of therapy. Secondary objectives include analysing effects on kidney function, the frequency of urolithiasis, and treatment tolerance. Additionally, in-depth metabolomics analyses will explore pathophysiological pathways during treatment. Investigators, patients, and research staff will be blinded to the randomization list. This study was initially registered under EudraCT (Nr:2022-000994-13) and has been transitioned to CTIS (Nr: 2024-519371-25-00) to comply with EU Regulation 536/2014, ensuring streamlined management and transparency. Discussion Dapagliflozin’s pleiotropic effects may provide a novel prophylactic treatment option for urolithiasis. This study aims to evaluate potential treatment effects in a prospective RCT and elucidate potential pathophysiological pathways through in-depth metabolomics analyses. SGLT-2 inhibitors have the potential to transform the landscape of urolithiasis treatment, reduce the healthcare burden on individuals and the system, and significantly improve patient quality of life.